Artemisinin, as an antimalarial compound, of Artemisia annua L. growing wild in north of Iran. - H Lari yazdi; RA Khavarinejad; AH Roustaian (Institue of Medicinal Plants, ACECR, 2002)
Artemisinin is an antimalarial compound that is naturally found in A.annua L. (Asteraceae) The leaves of A.annua L. growing wild in the north of Iran are collected and extracted for measuring artemisinin by HPLC. The most amount of artemisinin(0.097%) was found in the sample collected from Macaroud and the lowest amount (0.024%) belonged to the sample grown in Doab.